Use of ischemia modified albumin for the diagnosis of myocardial infarction - Nariélle F. Bonorino; Adroaldo Lunardelli; Jarbas R. Oliveira (Sociedade Brasileira de Patologia Clínica, 2015)
ABSTRACT Introduction: Literature reports addressing ischemia modified albumin (IMA) as a good marker for the early diagnosis of myocardial ischemia through albumin cobalt binding (ACB) test, that is before myocardial infarction (MI) occurs. Objective: To evaluate the IMA plasmatic levels in infarcted patients, in order to verify its potential as an early marker for early diagnosis of MI, investigate its correlation with existing cardiac biomarkers such as total creatine kinase (CK) and creatine kinase-MB fraction (CK-MB), as well as to assess the correlation between IMA and oxidative stress. Methods: The sample was divided into two groups according to serum troponin I (TnI) results; one group of infarcted patients (with MI) (TnI levels higher than 0.05 ng/ml), and the other group of non-infarcted patients (without MI) (TnI levels lower than 0.05 ng/ml). The results of total CK, CK-MB, thiobarbituric acid reactive substances (TBARS), and IMA were analyzed in both groups. Results: Regarding the existing cardiac markers, there was a significant increase of total CK and CK-MB levels in With MI group. In relation to the oxidative stress parameter, a significant increase was observed in with MI group compared to without MI group. However, IMA showed no significant difference between the groups; and also there was no significant correlation between IMA and the cardiac markers. There was no correlation between IMA and TBARS. Conclusion: Our results suggest that IMA cannot be used alone for the diagnosis of MI.